Konsep Pemikiran Pendidikan Islam Abdullah Nashih Ulwan dan Ahmad Hassan serta Relevansinya dengan Pendidikan Saat Ini - Kholil, A. Munawar; Rahman, Abdur; Khoir, Mulyanto Abdullah (TSAQOFAH, 2024)
Abdullah Nashih Ulwan and Ahmad Hassan are prominent thinkers in Islamic education who have long been involved in the field. Many of their works have been translated into Indonesian and can be studied and used as references. According to both, the concept of good education is one that produces children who are obedient and diligent in carrying out Allah's commands and avoiding His prohibitions, based on Islamic values, and embracing Islam as their religion. They also emphasize that the foundation of all educational activities should be the Qur'an and Hadith rather than other sources. They advocate for a curriculum that is integrated and comprehensive, with the Qur'an and Hadith as the primary sources in its formulation. The thoughts of Abdullah Nashih Ulwan and Ahmad Hassan are highly relevant to contemporary education, aiming to create education with the primary goal of fostering students to embrace monotheism, derive all sources from Islamic teachings, and cultivate students' morals so that their interactions do not deviate from Islamic guidance.